2023
DOI: 10.1038/s41467-023-40349-z
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Afatinib for stage III EGFR-mutant non-small cell lung cancer: a phase II study

Abstract: Afatinib, an irreversible ErbB-family blocker, could improve the survival of advanced epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer patients (NSCLCm+). This phase II trial (NCT04201756) aimed to assess the feasibility of neoadjuvant Afatinib treatment for stage III NSCLCm+. Forty-seven patients received neoadjuvant Afatinib treatment (40 mg daily). The primary endpoint was objective response rate (ORR). Secondary endpoints included pathological complete response (pCR) rate, patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Indeed, several other early studies also demonstrated potential use of targeted therapies in preoperative studies. NCT03433469 using 2 cycles of neoadjuvant osimertinib in stage IA-IIIA NSCLC with EGFR mutations demonstrated 15% mPR and 44% achieved lymph node downstaging [ 24 ] as well as NCT04201756 which utilized 2 to 4 cycles of neoadjuvant afatinib, achieved 9.1% mPR and 57.6% had pathological downstaging for stage III NSCLC [ 25 ]. Combinatory studies using targeted therapies with or without chemotherapy are also being explored: NCT04351555 (NeoADAURA; phase III osimertinib vs. osimertinib plus PDC vs. placebo plus PDC neoadjuvantly followed by physician’s choice adjuvant treatment of targeted therapy with or without chemotherapy) [ 26 ], NCT04302025 (NAUTIKA1; single arm phase II neoadjuvant use of alectinib for 8 weeks) [ 27 ], and NCT05015010 (ALNEO; single arm phase II neoadjuvant use of alectinib for 2 cycles followed by adjuvant use up to 24 cycles) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several other early studies also demonstrated potential use of targeted therapies in preoperative studies. NCT03433469 using 2 cycles of neoadjuvant osimertinib in stage IA-IIIA NSCLC with EGFR mutations demonstrated 15% mPR and 44% achieved lymph node downstaging [ 24 ] as well as NCT04201756 which utilized 2 to 4 cycles of neoadjuvant afatinib, achieved 9.1% mPR and 57.6% had pathological downstaging for stage III NSCLC [ 25 ]. Combinatory studies using targeted therapies with or without chemotherapy are also being explored: NCT04351555 (NeoADAURA; phase III osimertinib vs. osimertinib plus PDC vs. placebo plus PDC neoadjuvantly followed by physician’s choice adjuvant treatment of targeted therapy with or without chemotherapy) [ 26 ], NCT04302025 (NAUTIKA1; single arm phase II neoadjuvant use of alectinib for 8 weeks) [ 27 ], and NCT05015010 (ALNEO; single arm phase II neoadjuvant use of alectinib for 2 cycles followed by adjuvant use up to 24 cycles) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such adverse effects complicate the identification of tumor margins and relevant anatomical structures during operative procedures, thus increasing the risk of intraoperative bleeding and the complexity of postoperative recovery. 10 …”
Section: Introductionmentioning
confidence: 99%